2017
DOI: 10.1111/zph.12374
|View full text |Cite
|
Sign up to set email alerts
|

Recreational sandboxes for children and dogs can be a source of epidemic ribotypes of Clostridium difficile

Abstract: Different studies have suggested that the sand of public playgrounds could have a role in the transmission of infections, particularly in children. Furthermore, free access of pets and other animals to the playgrounds might increase such a risk. We studied the presence of Clostridium difficile in 20 pairs of sandboxes for children and dogs located in different playgrounds within the Madrid region (Spain). Clostridium difficile isolation was performed by enrichment and selective culture procedures. The genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Studies addressing the presence of C. difficile in the natural environment are less numerous than those investigating the bacterium in foods and animals (Rodriguez et al, ). There are recent studies describing its presence in wastewater treatment plants or rivers (Moradigaravand et al, ; Zidaric et al, ), with some of them performed in soil farms (Bäverud et al, ) and in other rural areas (Janezic et al, ; Simango, ) or public environments (Al‐Saif & Brazier, ; Moono et al, ; Orden et al, ). Wastewater treatment plants are highly contaminated, with up to 96% of samples being positive (Romano et al, ; Xu, Weese, Flemming, Odumeru, & Warriner, ; Nikaeen, Aghili‐Dehnavi, Hssanzadeh, & Jalali, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies addressing the presence of C. difficile in the natural environment are less numerous than those investigating the bacterium in foods and animals (Rodriguez et al, ). There are recent studies describing its presence in wastewater treatment plants or rivers (Moradigaravand et al, ; Zidaric et al, ), with some of them performed in soil farms (Bäverud et al, ) and in other rural areas (Janezic et al, ; Simango, ) or public environments (Al‐Saif & Brazier, ; Moono et al, ; Orden et al, ). Wastewater treatment plants are highly contaminated, with up to 96% of samples being positive (Romano et al, ; Xu, Weese, Flemming, Odumeru, & Warriner, ; Nikaeen, Aghili‐Dehnavi, Hssanzadeh, & Jalali, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, C. difficile was reported to be present in 68% of positive samples from rivers near densely populated areas, with the same predominant ribotypes found in hospitals (Zidaric et al, ). Regarding public environments, such as parks and other playgrounds, the available data are not yet conclusive, since the reported prevalence varies from zero detection to 52% (Al‐Saif & Brazier, ; Orden et al, ). In this study, the overall prevalence found (40.2%) matched with the data reported previously from environmental samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For those with no exposure to HA sources of infection, a potential source of CA-CDI could be environmental exposures, including food, compost, animals, and public sandboxes; over 50% of samples from public sandboxes in a Madrid study were positive for C. difficile, and seven of eight toxigenic samples were epidemic RTs 014 or 106. 47 The RT/strain of C. difficile may vary between HA-CDI and CA-CDI as well. 45 In efforts to identify modifiable risk factors and provide risk stratification, recent research efforts have focused on concomitant medication use, as well as identifying specific strains, and RTs of C. difficile.…”
Section: Recurrent CDImentioning
confidence: 99%